Multi-Omics Investigations Revealed Underlying Molecular Mechanisms Associated With Tumor Stiffness and Identified Sunitinib as a Potential Therapy for Reducing Stiffness in Pituitary Adenomas - Wang, Zihao; Chang, Mengqi; Zhang, Yanruo; Zhou, Gang; Liu, Penghao; Lou, Jizhong; Wang, Yuekun; Zhang, Yuan; Guo, Xiaopeng; Wang, Yaning; Bao, Xinjie; Lian, Wei; et al. (Frontiers in Cell and Developmental Biology, 2022)
Purpose: Pituitary adenomas (PAs) are the second most common intracranial neoplasms. Total surgical resection was extremely important for curing PAs, whereas tumor stiffness has gradually become the most critical factor affecting the resection rate in PAs. We aimed to investigate the molecular mechanisms of tumor stiffening and explore novel medications to reduce stiffness for improving surgical remission rates in PA patients. Methods: RNA sequencing, whole-genome bisulfite sequencing, and whole exome sequencing were applied to identify transcriptomic, epigenomic, and genomic underpinnings among 11 soft and 11 stiff PA samples surgically resected from patients at Peking Union Medical College Hospital (PUMCH). GH3 cell line and xenograft PA model was used to demonstrate therapeutic effect of sunitinib, and atomic force microscopy (AFM) was used to detect the stiffness of tumors. Results: Tumor microenvironment analyses and immunofluorescence staining indicated endothelial cells (ECs) and cancer-associated fibroblasts (CAFs) were more abundant in stiff PAs. Weighted gene coexpression network analysis identified the most critical stiffness-related gene (SRG) module, which was highly correlated with stiff phenotype, ECs and CAFs. Functional annotations suggested SRGs might regulate PA stiffness by regulating the development, differentiation, and apoptosis of ECs and CAFs and related molecular pathways. Aberrant DNA methylation and m6A RNA modifications were investigated to play crucial roles in regulating PA stiffness. Somatic mutation analysis revealed increased intratumoral heterogeneity and decreased response to immunotherapy in stiff tumors. Connectivity Map analysis of SRGs and pRRophetic algorithm based on drug sensitivity data of cancer cell lines finally determine sunitinib as a promising agent targeting stiff tumors. Sunitinib inhibited PA growth in vitro and in vivo, and also reduced tumor stiffness in xenograft PA models detected by AFM. Conclusion: This is the first study investigating the underlying mechanisms contributing to the stiffening of PAs, and providing novel insights into medication therapy for stiff PAs.